A global slamming force model for offshore wind jacket structures. (July 2018) - Tu, Ying; Cheng, Zhengshun; Muskulus, Michael
Abstract: Under certain harsh environmental conditions, jacket structures supporting offshore wind turbines might be exposed to plunging breaking waves, causing slamming forces that affect the structural integrity and fatigue life. The slamming forces should thus be properly considered during the design, but a suitable force model specifically for jacket structures is currently in absence. In this study, a five-parameter force model is developed for estimating global slamming forces due to plunging breaking waves on jacket structures, based on statistical analyses of experimental data from the WaveSlam project. The force model is developed by considering a total of 176 individual breaking waves, under six wave conditions. For each individual breaking wave, the time history of the slamming force is calculated based on hammer test data in addition to wave test data, and the wave parameters are acquired from a wave elevation measurement. The acquired time histories and wave parameters are then used to determine the parameters involved in the force model, including two exponential parameters (i.e. α 1 and α 2 ) and three dimensionless coefficients for the expressions of wave-dependent parameters (i.e. duration coefficient ζ 1, rising time coefficient ζ 2, and peak force coefficient ζ 3 ). It is found that α 1, α 2, ζ 1 and ζ 2 are approximately constant, and ζ 3 follows a lognormal distribution. The quantile that determines ζ 3 should be carefully selected so as to provide a conservative prediction. A quantile of 95% is suggested in this paper, and it is found to be conservative based on the verification of the developed force model. Therefore, for a given sea state, this force model can give a deterministic and conservative prediction of the slamming force time history, regardless of the randomness of slamming forces. Challenges for the application of the force model are also addressed. Highlights: A novel global slamming force model for offshore wind jacket structures. The model is developed based on the data under varied wave conditions from the large-scale WaveSlam experiment. The model provides a full description of the time series of global slamming forces. The model is validated against experimental data. The model is simple to use in the design practice of offshore wind jacket structures.